2002
DOI: 10.1080/13682820110116794
|View full text |Cite
|
Sign up to set email alerts
|

Mother‐child interactions in Canada and Italy: Linguistic responsiveness to late‐talking toddlers

Abstract: The aim was to examine cross-cultural variation in linguistic responsiveness to young children in 10 English-speaking mother-child dyads and 10 Italian-speaking mother-child dyads. All 20 children were late talkers who possessed delays in expressive vocabulary development but age-appropriate cognitive and receptive language skills. Dyads were filmed in 15-minute free play contexts, which were transcribed and coded for measures of maternal linguistic input (e.g. rate, MLU, labels, expansions) and child language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 48 publications
1
52
1
3
Order By: Relevance
“…One particular intervention, dialogic reading , incorporates many specific adult behaviors into target child communication attempts to support language development in the context of JBR (Whitehurst, Falco, Lonigan, & Fischel, 1988). Higher level FLTs such as expansions (i.e., extending a child’s utterance) and open-ended questions (i.e., asking why and how questions) seem to elicit more words from children who are at the early word phrase level of language development (Mol, Bus, DeJong, & Smeets, 2008; Whitehurst et al, 1988), while lower level FLTs such as linguistic mapping (i.e., putting child’s unintelligible utterance into words) and imitation (i.e., repeating the child’s utterance verbatim) may enhance language skills in younger populations of children at the prelinguistic stage of development (Girolametto et al, 2002; Yoder, McCathren, Warren, & Watson, 2001). Evidence-based research in dialogic reading techniques has shown dramatic improvements in oral language development for children who are at risk for language delays (Bus, 2001; Institute of Education Sciences, 2010).…”
Section: Jbr and Children With Nhmentioning
confidence: 99%
“…One particular intervention, dialogic reading , incorporates many specific adult behaviors into target child communication attempts to support language development in the context of JBR (Whitehurst, Falco, Lonigan, & Fischel, 1988). Higher level FLTs such as expansions (i.e., extending a child’s utterance) and open-ended questions (i.e., asking why and how questions) seem to elicit more words from children who are at the early word phrase level of language development (Mol, Bus, DeJong, & Smeets, 2008; Whitehurst et al, 1988), while lower level FLTs such as linguistic mapping (i.e., putting child’s unintelligible utterance into words) and imitation (i.e., repeating the child’s utterance verbatim) may enhance language skills in younger populations of children at the prelinguistic stage of development (Girolametto et al, 2002; Yoder, McCathren, Warren, & Watson, 2001). Evidence-based research in dialogic reading techniques has shown dramatic improvements in oral language development for children who are at risk for language delays (Bus, 2001; Institute of Education Sciences, 2010).…”
Section: Jbr and Children With Nhmentioning
confidence: 99%
“…318,320,321 Parents-as-aides conceptualises parents as assuming an active role in supporting implementation of therapy objectives. In this instance, SLTs often provide home activities for parents to reinforce learning that has taken place during therapist-led intervention with the child.…”
Section: Introductionmentioning
confidence: 99%
“…Dependent variables were children's topic extensions, verbal topic maintaining responses, non-verbal topic maintaining responses and non-relevant responses. The coding system used was adapted from Keenan and Schieffelin (1976), Brinton and Fujiki (1984), Fey (1986), Girolametto (1988), Girolametto, Bonifacio, Visini, Weitzman, Zocconi, and Pearce (2002), Girolametto, Sussman, and Weitzman (2007), Tannock (1988) and Roberts et al (2007). Table III summarises the coding categories and provides examples of the conversational turns.…”
Section: Methodsmentioning
confidence: 99%